Neurilemmoma of maxillary alveolus: A rare case report and review of literature - Saravanan Kandasamy; R Senthil Nathan; Reena Rachel John (Wolters Kluwer Medknow Publications, 2017)
Schwannomas or neurilemmomas are benign, slow growing, usually solitary and encapsulated tumor, originating from Schwann cells of the nerve sheath. Intraoral schwannomas account for 1% of head and neck region and are commonly seen at the base of the tongue. Most of the literature, reports of schwannomas in the tongue region are common. In this article we report a rare occurrence of schwannoma in the maxillary alveolus region and its management. A 45 year old female patient reported to the department of oral and maxillofacial surgery with a complaint of swelling in the left maxillary alveolus in relation to molar teeth that had been present for more than 3 months. Apparently the swelling was small one initially, which gradually increased in size. Such a rare cas e of intraoral schwannoma should be followed up periodically to look for any malignant transformation and recurrences. An important conclusion that has evolved from the reviewed articles, is that the differential diagnosis of painless nodules in head and neck must include schwannomas.